Analysis of Code Switching on Cinta Laura Kiehl in Iwil Network Youtube Channel Video - Patricia Lestuny, Fernanda; Irwandika, Gede (Asian Journal of Social and Humanities, 2024)
The study, "An Analysis of Code Switching on Cinta Laura Kiehl in Iwil Network YouTube Channel Video," focused on two main issues: types and reasons for code switching. Utilizing Poplack's (1980) and Grosjean's (1981) theories, it employed a qualitative approach. Data collection involved downloading the video, watching the podcast, reading the script, and identifying instances of code switching. A total of 144 instances were found, categorized into 21 Tag Switching, 91 Inter-Sentential, and 32 Intra-Sentential occurrences. Reasons for code switching included Fill a Linguistics Need for Lexical Item, Set Phrase, Discourse Maker, or Sentence Filler (72 instances), Continued The Last Language Used (52 instances), and others such as Quoting Someone (1 instance), Specify Address (3 instances), and Conveying Confidentiality, Anger, and Annoyance (4 instances). These findings contribute to understanding the intricacies of code switching in the context of Cinta Laura Kiehl's videos on the Iwil Network YouTube channel.